Advocacy processes in mental health: a qualitative study. Issue 2 (3rd April 2017) - Stomski, Norman; Morrison, Paul; Whitely, Martin; Brennan, Pip
ABSTRACT: Advocates perform an important role in representing the rights of mental health consumers, especially since mental health consumers are often marginalized. Little is known about the processes advocates use to assist mental health consumers in navigating the health care system. This study details the manner in which advocates work together with mental health consumers and health professionals through presenting a qualitative synthesis of 60 case records. Four main themes emerged: negotiating on behalf of consumers during meetings with health professionals; liaising between consumers and health professionals outside of meetings; supporting consumer decision making without the involvement of health professionals; and involvement in legal processes. The findings of this study demonstrated that advocates were primarily oriented toward the protection of negative rights, but they also promoted positive rights.